The current situation in hip arthroscopy - Marin-Peña, O (2017)
Hip arthroscopy is an evolving surgical technique that has recently increased in popularity.Although femoroacetabular impingement was an important launch pad for this technique, extra-articular pathology has been described through hip endoscopy.Good clinical results in the medium term will allow improvements in this technique and increase its indications. Cite this article: EFORT Open Rev 2017;2:58-65. DOI: 10.1302/2058-5241.2.150041.